High-entropy oxide and application thereof in preparation of supercapacitor
By synthesizing high-entropy oxide nanocrystals using boron doping and functionalized graphene quantum dots, the problems of low synthesis efficiency and poor conductivity of high-entropy oxides in supercapacitor applications are solved, and high energy density and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411839731.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The application of high-entropy oxides in high-performance supercapacitors faces four key challenges: the synthesis method is low efficiency and high cost, and is not suitable for large-scale production; the inability to effectively tune the nanocrystal morphology and structure; the metal element composition design is not conducive to efficient hybrid capacitor deionization; and the electron/ion conductivity is poor.
By synthesizing (Nb0.32V0.17Mo0.17W0.17Co0.17)2O4 high-entropy oxide nanocrystals using boron doping and histidine and serine functionalized graphene quantum dots (BHS-GQD), the atomic water dispersion of all metal elements in solution and solid states was achieved, and long-range ordered nanocrystals with interconnected tunnels were prepared.
The electrochemical performance of high entropy oxides is significantly improved, and the supercapacitors exhibit high energy density (up to 153Wh/Kg at 900W/Kg), and improve electron/ion conductivity.
Smart Images

Figure CN119797913A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high entropy oxide and application thereof in preparing a supercapacitor, belonging to the technical field of supercapacitors. Background Art
[0002] In the face of increasingly serious environmental pollution and energy crisis, it is crucial to develop efficient energy storage and conversion devices. Supercapacitors are electrochemical devices that bridge the gap between batteries and traditional capacitors. They have high power density (2-10kW / kg), fast charge / discharge speed, and long service life (10 4 -10 6 cycle) and has attracted widespread attention.
[0003] Supercapacitors are divided into two categories, namely double-layer capacitors and pseudocapacitors. The materials used in double-layer capacitors (such as carbonaceous materials) have a significant impact on the establishment of their cycle stability, while the materials used in pseudocapacitors are transition metal oxides and conductive polymers with multiple oxidation transition states, which have high capacitance in the field of energy storage. Transition metal oxides have excellent oxidation and reduction reversible properties in a wider potential range, which is very beneficial in supercapacitor applications. However, transition metal oxides have poor conductivity and severe structural disintegration during the reaction process, which hinders their application in high-performance supercapacitors.
[0004] High entropy oxides are single-phase oxides formed by solid solution of at least five metals in an equimolar or nearly molar ratio in the same sublattice. config )≥1.5R. High entropy oxides break the solid solubility limit between traditional oxide elements, and produce high entropy effect, cocktail effect, slow diffusion effect and lattice distortion effect in a variety of elemental properties with different and highly disordered combinations. Compared with traditional oxides, high entropy effect and slow diffusion effect jointly inhibit the structural phase transition of materials during electrochemical testing, and cocktail effect and lattice distortion produce defect engineering to synergistically provide sufficient active sites and improve electronic conductivity, which respectively lead to higher material structural stability and storage capacity.
[0005] However, the poor structural uniformity and conductivity of high-entropy oxides limit their practical application in high-performance supercapacitors. Due to the entropic interactions between the constituent elements and the random distribution of multiple elements with different atomic radii, a large number of studies have shown that the synthesis of high-entropy oxide solid solutions with random element distribution generally exhibits significant short-range ordered structural heterogeneity. This heterogeneity directly affects the distribution, abundance and properties of electrochemically active sites, leading to different chemical environments and energy storage pathways.
[0006] Wang et al. reported a high-temperature strategy for preparing Mg 0.2 Co 0.2Ni 0.2 Cu 0.2 Zn 0.2 HEO single-phase nano high entropy oxide. Abdelhafiz et al. prepared (FeNiCoCr)acet single-phase nano high entropy oxide by pulsed photosynthesis. Although the synthesis technology of single-phase nano high entropy oxide has made significant progress, the practical application of HEO electrode materials in high-performance supercapacitors still faces four key challenges: (1) The current synthesis method is not suitable for large-scale production of HEO nanoparticles due to the requirement for dedicated equipment, low efficiency and high cost; (2) The current synthesis method cannot achieve effective tuning of the morphology and nanostructure of HEO nanocrystals; (3) The current design of the metal element composition in HEO electrode materials is not conducive to efficient hybrid capacitor deionization; (4) Due to the lack of effective electronic and ion channels, the electronic / ionic conductivity of current HEO electrode materials is poor.
[0007] Therefore, developing a method that can prepare single-phase nano high-entropy oxide at a relatively low temperature and use it to prepare high-performance supercapacitors has extremely high practical and economic value. Summary of the invention
[0008] In order to solve the above problems, the present invention uses boron doped and histidine and serine functionalized graphene quantum dots (BHS-GQD) to synthesize (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 High entropy oxide nanocrystals achieve uniform atomic dispersion of all metal elements in solution and solid state. The high entropy oxide structure prepared by the present invention is a long-range ordered (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 Nanocrystals have significantly improved electrochemical performance.
[0009] A first object of the present invention is to provide a method for preparing a high entropy oxide, the method comprising:
[0010] (1) mixing a cobalt ion salt, a tungsten ion salt, a vanadium ion salt, a niobium ion salt and a molybdenum ion salt in a molar ratio of 0.15-0.2:0.15-0.2:0.15-0.2:0.31-0.34:0.15-0.2, dissolving the mixture in a graphene quantum dot solution, and stirring the mixture to obtain a mixed solution;
[0011] (2) using cotton to absorb the mixed solution and drying to obtain cotton adsorbed with metal ions and graphene quantum dots; wherein the mass ratio of metal salt, graphene quantum dots and cotton is 0.8-1.2:0.6-1.2:0.9-1.3;
[0012] (3) Cotton adsorbed with metal ions and graphene quantum dots is annealed to prepare high entropy oxide.
[0013] In one embodiment, the method for preparing graphene quantum dots comprises:
[0014] One or more of citric acid, serine, histidine and boric acid are dissolved in water and heated for reaction to obtain;
[0015] Optionally, citric acid is dissolved in water, and the ratio of citric acid to water is 18-19.5 g: 45-60 mL;
[0016] Optionally, citric acid, serine and histidine are dissolved in water, and the ratio of citric acid, serine, histidine and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 45-60 mL;
[0017] Optionally, citric acid, serine, histidine and boric acid are dissolved in water, and the dosage ratio of citric acid, serine, histidine, boric acid and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 0.8-1.5 g: 45-60 mL;
[0018] Optionally, the heating reaction is carried out at 170-200° C. for 2-4 hours.
[0019] In one embodiment, the molar ratio in step (1) is also the molar ratio of cobalt ions, tungsten ions, vanadium ions, niobium ions and molybdenum ions.
[0020] In one embodiment, the cobalt ion salt includes one or more of cobalt chloride, cobalt nitrate, and cobalt sulfate;
[0021] The tungsten ion salt includes one or more of tungsten hexachloride, sodium metatungstate, and sodium tungstate dihydrate;
[0022] The vanadium ion salt includes one or more of vanadium chloride, ammonium metavanadate, and sodium vanadate hydrate;
[0023] The niobium ion salt includes one or more of niobium chloride, niobium oxalate, and ammonium niobate oxalate hydrate;
[0024] The molybdenum ion salt includes one or more of sodium molybdate, molybdenum pentachloride, and ammonium molybdate.
[0025] In one embodiment, the annealing is carried out at 800-900° C. for 2-5 hours.
[0026] In one embodiment, the stirring is performed at 400-600 rpm.
[0027] The second object of the present invention is to provide a high entropy oxide prepared by any of the above methods.
[0028] The third object of the present invention is to provide the use of any of the above methods or the above high entropy oxides in the preparation of electronic components.
[0029] In one embodiment, the electronic components include batteries and capacitors.
[0030] A fourth object of the present invention is to provide any supercapacitor, wherein the preparation method of the supercapacitor comprises:
[0031] The high entropy oxide, carbon black and polyvinylidene fluoride are dispersed in n-methyl-2-pyrrolidone to obtain an electrode slurry; the electrode slurry is coated on the surface of a titanium sheet to obtain an electrode sheet; two electrode sheets are used as electrodes, PVA / Li 2 SO 4 The gel is used as an electrolyte to form a symmetrical solid-state supercapacitor;
[0032] Optionally, the mass ratio of high entropy oxide, carbon black and polyvinylidene fluoride is 70-90:5-15:5-15;
[0033] Optionally, the mass density of the electrode slurry on the surface of the electrode sheet is 1.5 to 2.5 mg / cm.
[0034] In one embodiment, PVA / Li 2 SO 4 The gel preparation method includes:
[0035] 1-3 g polyvinyl alcohol (PVA) and 8-12 mL 1-3 mol / L Li 2 SO 4 The solution was poured into 10-30 mL of water and stirred at 70-75 °C until the solution became clear and transparent. After cooling to room temperature, PVA / Li 2 SO 4 gel.
[0036] A fifth object of the present invention is to provide a method for improving the performance of a supercapacitor, wherein a supercapacitor is prepared using a high entropy oxide; the preparation method of the high entropy oxide comprises:
[0037] (1) mixing a cobalt ion salt, a tungsten ion salt, a vanadium ion salt, a niobium ion salt and a molybdenum ion salt in a molar ratio of 0.15-0.2:0.15-0.2:0.15-0.2:0.31-0.34:0.15-0.2, dissolving the mixture in a graphene quantum dot solution, and stirring the mixture to obtain a mixed solution;
[0038] (2) Using cotton to absorb the mixed solution and drying to obtain cotton adsorbed with metal ions and graphene quantum dots; wherein the mass ratio of metal salt, graphene quantum dots and cotton is 0.8-1.2:0.6-1.2:0.9-1.3
[0039] (3) Cotton adsorbed with metal ions and graphene quantum dots is annealed to prepare high entropy oxide.
[0040] In one embodiment, the method for preparing graphene quantum dots comprises:
[0041] One or more of citric acid, serine, histidine and boric acid are dissolved in water and heated for reaction to obtain;
[0042] Optionally, citric acid is dissolved in water, and the ratio of citric acid to water is 18-19.5 g: 45-60 mL;
[0043] Optionally, citric acid, serine and histidine are dissolved in water, and the ratio of citric acid, serine, histidine and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 45-60 mL;
[0044] Optionally, citric acid, serine, histidine and boric acid are dissolved in water, and the dosage ratio of citric acid, serine, histidine, boric acid and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 0.8-1.5 g: 45-60 mL;
[0045] Optionally, the heating reaction is carried out at 170-200° C. for 2-4 hours.
[0046] In one embodiment, the cobalt ion salt includes one or more of cobalt chloride, cobalt nitrate, and cobalt sulfate;
[0047] The tungsten ion salt includes one or more of tungsten hexachloride, sodium metatungstate, and sodium tungstate dihydrate;
[0048] The vanadium ion salt includes one or more of vanadium chloride, ammonium metavanadate, and sodium vanadate hydrate;
[0049] The niobium ion salt includes one or more of niobium chloride, niobium oxalate, and ammonium niobate oxalate hydrate;
[0050] The molybdenum ion salt includes one or more of sodium molybdate, molybdenum pentachloride, and ammonium molybdate.
[0051] In one embodiment, the annealing is carried out at 800-900° C. for 2-5 hours.
[0052] Beneficial Effects of the Invention
[0053] The present invention uses boron doped and histidine and serine functionalized graphene quantum dots (BHS-GQD) to synthesize (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 High entropy oxide nanocrystals achieve uniform atomic dispersion of all metal elements in solution and solid state. At the same time, the high entropy oxide structure prepared by the present invention is a long-range ordered (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 Nanocrystals have significantly improved electrochemical performance.
[0054] Specifically, supercapacitors (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 / / (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 It shows a higher energy density (up to 153W h / Kg at 900W / Kg). BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -SEM image of GQDs.
[0056] Figure 2 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 )2 O 4 -SEM image of HS-GQDs.
[0057] Figure 3 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -SEM image of BHS-GQDs.
[0058] Figure 4 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -XRD pattern of GQDs.
[0059] Figure 5 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -XRD pattern of HS-GQDs.
[0060] Figure 6 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -XRD pattern of BHS-GQDs.
[0061] Figure 7 The crystal structure of space group I-4 (PDF#081-2343).
[0062] Figure 8 The crystal structure of the space group P42 / mnm (PDF#075-2340).
[0063] Fig. 9 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD electrochemical impedance spectroscopy combined diagram; a is (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -Electrochemical impedance curve of BHS-GQD; b is (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD electrochemical impedance curve; c is (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD electrochemical impedance curve.
[0064] Fig.10 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -Charge-discharge curves of the GQD electrode measured at different current densities.
[0065] Fig.11 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -Charge and discharge curves of HS-GQD electrode measured at different current densities.
[0066] Fig.12 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4-Charge and discharge curves of BHS-GQD electrode measured at different current densities.
[0067] Fig.13 Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -Cyclic voltammetry curves of BHS-GQD electrode measured at different scan rates.
[0068] Fig.14 For supercapacitor (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD / / (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -Energy density of BHS-GQD at different power densities. DETAILED DESCRIPTION
[0069] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0070] Test method:
[0071] The preparation process of the electrochemical impedance spectroscopy electrode is as follows:
[0072] A mixture of high entropy oxide and polyvinylidene fluoride was dispersed in n-methyl-2-pyrrolidone at a mass ratio of 80:10 to form a uniform electrode slurry. The electrode slurry was then coated on a 1 cm×1 cm conductive glass surface by a scraping method and dried in a vacuum drying oven at 80°C for 24 hours to prepare an electrochemical impedance spectroscopy electrode.
[0073] The raw materials used in the examples are:
[0074] Citric acid, serine, histidine, boric acid, cobalt chloride (CoCl 2 6H 2 O) and sodium tungstate (Na 2 WO 4 ·2H 2 O) was purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd., China; ammonium metavanadate (NH 4 VO 3) and niobium oxalate (Nb(HC 2 O 4 ) 5 ) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; ammonium molybdate (H 24 Mo 7 N 6 O 24 ·2H 2 O) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., China.
[0075] Example 1: Preparation of graphene quantum dots doped with different elements
[0076] 1. Preparation of undoped graphene quantum dots (GQD)
[0077] 19.2 g of citric acid was weighed and ultrasonically dissolved in 50 mL of ultrapure water, poured into a 200 mL polytetrafluoroethylene reactor, and then reacted in a 175° C. forced air drying oven for 6 hours; after the reactor was cooled to room temperature, the liquid was collected and freeze-dried to obtain a GQD solid.
[0078] 2. Preparation of N-doped graphene quantum dots (HS-GQD)
[0079] 19.2 g of citric acid, 2.1 g of serine and 15.5 g of histidine were weighed and ultrasonically dissolved in 50 mL of ultrapure water, poured into a 200 mL polytetrafluoroethylene reactor, and then reacted in a forced air drying oven at 175 ° C for 6 hours; after the reactor was cooled to room temperature, the liquid was collected and freeze-dried to obtain HS-GQD solid.
[0080] 3. Preparation of N and B atom-doped graphene quantum dots (BHS-GQD)
[0081] 19.2 g of citric acid, 2.1 g of serine, 15.5 g of histidine and 1.2 g of boric acid were weighed and ultrasonically dissolved in 50 mL of ultrapure water, poured into a 200 mL polytetrafluoroethylene reactor, and then reacted in a forced air drying oven at 175 ° C for 6 hours; after the reactor was cooled to room temperature, the liquid was collected and freeze-dried to obtain BSH-GQD solid.
[0082] Example 2: Preparation of high entropy oxide
[0083] The graphene quantum dots GQD, HS-GQD and BHS-GQD prepared in Example 1 were used to prepare high entropy oxides.
[0084] Preparation (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O4 -GQD
[0085] (1) 1 g GQD, 10 mL 30 wt.% H 2 O 2 Pour 2 mL of ammonia water into 60 mL of ultrapure water and ultrasonicate for 20 minutes to obtain a graphene quantum dot GQD solution;
[0086] (2) Weigh 0.17 mol CoCl 2 6H 2 O, 0.17 mol Na 2 WO 4 ·2H 2 O, 0.17 mol NH 4 VO 3 、0.32mol Nb(HC 2 O 4 ) 5 and 0.024H 24 Mo 7 N 6 O 24 ·2H 2 O was added to the solution obtained in the above process (1) (i.e., graphene quantum dot GQD solution), and stirred at 500 rpm for 3 hours to obtain a mixed solution;
[0087] (3) Weigh 1 g of cotton and spread it on a watch glass. Pour the solution (mixed solution) obtained in the above process (2) into the cotton. After the cotton is completely absorbed, place it in a drying oven at 60°C for drying.
[0088] (4) The dried product was placed in a tubular furnace under a nitrogen environment for high temperature annealing at a heating rate of 5°C / min and kept at 850°C for 3 hours to obtain a high entropy oxide named (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD.
[0089] Based on the above method, GQDs were replaced by HS-GQDs and BHS-GQDs, respectively, to prepare high entropy oxides (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W0.17 Co 0.17 ) 2 O 4 -BHS-GQD. Example 3: Morphological detection of high entropy oxide composites of different graphene quantum dots
[0090] Take the high entropy oxide (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD, and detect its morphological characteristics.
[0091] 1. Scanning electron microscope (SEM)
[0092] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD morphological characteristics such as Figure 1 As shown;
[0093] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -The morphological characteristics of HS-GQDs are as follows Figure 2 As shown;
[0094] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BSH-GQD morphological characteristics such as Figure 3 shown.
[0095] SEM results show that (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -SH-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BSH-GQDs have obvious differences in morphology.
[0096] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -SH-GQDs are all cubic in shape, but (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD has rounded corners, while (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -The corners of SH-GQD are sharp.
[0097] and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD and (Nb 0.32 V 0.17 Mo0.17 W 0.17 Co 0.17 ) 2 O 4 -SH-GQD is different, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 The morphology of -BSH-GQDs is fish-shaped.
[0098] The above results show that undoped graphene quantum dots, N atom-doped graphene quantum dots and N and B atom-co-doped graphene quantum dots can induce high entropy oxide complexes of different forms; among them, the morphological features induced by N and B atom-co-doped graphene quantum dots are more uniform.
[0099] 2. X-ray diffraction (XDR)
[0100] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -XRD of GQDs Figure 4 As shown;
[0101] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -XRD of HS-GQDs Figure 5 As shown;
[0102] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -XRD patterns of BSH-GQDs Figure 6 shown.
[0103] XRD results show that (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, (Nb 0.32 V 0.17 Mo0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 There are obvious differences in the space groups of -BSH-GQDs.
[0104] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -SH-GQDs all exist in two space groups: P42 / mnm (PDF#075-2340) and I-4 (PDF#081-2343);
[0105] In (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -The ratio of P42 / mnm in HS-GQDs is much higher than that in I-4;
[0106] In (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQDs only have a single P42 / mnm space group.
[0107] The above results show that undoped graphene quantum dots, N atom-doped graphene quantum dots and N and B atom-co-doped graphene quantum dots can make high entropy oxides produce different space groups; compared with undoped graphene quantum dots and N atom-doped graphene quantum dots, N and B atom-co-doped graphene quantum dots can obtain single-phase high entropy oxides.
[0108] Among them, the crystal structure corresponding to the space group I-4 (PDF#081-2343) is as follows Figure 7 As shown, it indicates short-range order.
[0109] The crystal structure of the space group P42 / mnm (PDF#075-2340) is as follows Figure 8 As shown, it indicates long-range order.
[0110] Combined with the crystal structure, it can be seen that (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQDs have both short-range ordered and long-range ordered crystal structures, that is, these two high-entropy oxide composites have obvious structural heterogeneity; while (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BSH-GQD only has a long-range ordered crystal structure, that is, N, B co-doped graphene quantum dots induce a structurally homogeneous high-entropy oxide.
[0111] Example 4: Electrochemical impedance of high entropy oxide composites of different graphene quantum dots
[0112] Take the (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD), and the electrochemical impedance spectroscopy results are shown in Fig. 9 shown.
[0113] The results show that among the three materials, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD) has the smallest electron transfer resistance and the fastest ion diffusion rate. This shows that boron-doped and histidine- and serine-functionalized graphene quantum dots can significantly improve the conductivity of high-entropy oxide composites.
[0114] Example 5: Preparation of high entropy oxide electrodes
[0115] 1. Preparation of high entropy oxide electrodes
[0116] Take the high entropy oxide (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD, preparation of electrodes.
[0117] High entropy oxide (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD, carbon black and polyvinylidene fluoride were dispersed in n-methyl-2-pyrrolidone in a mass ratio of 80:10:10 to obtain a uniform electrode slurry; the electrode slurry was coated on the surface of a 1 cm × 1 cm titanium sheet by a doctor blade method, dried in a vacuum drying oven at 80°C for 24 hours, and then allowed to stand for 1 minute under a pressure of 5 MPa to prepare (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O4 -GQD working electrode sheet; the mass density of the electrode slurry on the electrode sheet is 2 mg / cm, and the surface area of the electrode sheet is 1 cm 2 .
[0118] According to the above method, the high entropy oxide composite (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD is (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD, respectively prepared (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD working electrode and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD working electrode sheet.
[0119] 2. Working electrode energy storage performance test
[0120] Take the (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD working electrode sheet, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD working electrode and (Nb 0.32 V0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD working electrode sheet, placed in 1 mol / L Li 2 SO 4 The electrodes were immersed in electrolyte for 24 hours to obtain activated working electrodes.
[0121] The three-electrode test system consists of an activated working electrode (1cm×2cm), a platinum counter electrode (1cm×1cm) and a saturated calomel reference electrode. The three-electrode test system uses 1 mol / L Li 2 SO 4 An aqueous solution serves as the electrolyte.
[0122] The three-electrode test system was used to detect (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD electrode sheet, (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -HS-GQD electrode and (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -Energy storage performance of BHS-GQD electrode sheet. The results are as follows.
[0123] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -The charge and discharge curves of the GQD electrode measured at different current densities are shown in Figure 2. Fig.10 As shown in the figure, the results show that when the charge and discharge current density is 1A / g, it can be calculated that (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -The specific capacity of the GQD electrode is as high as 468F / g.
[0124] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 The charge-discharge curves of the HS-GQD electrode at different current densities are shown in Figure 2. Fig.11 The results show that the specific capacity of the material is as high as 545.4F / g when the charge and discharge current density is 1A / g, which is higher than that of undoped graphene quantum dots (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 The capacity of the -GQD high-entropy oxide composite increased by 77.4 F / g.
[0125] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 The charge-discharge curves of the BHS-GQD electrode at different current densities are shown in Figure 2. Fig.12 The results show that the specific capacity of the material is as high as 966F / g when the charge and discharge current density is 1A / g, which is higher than that of undoped graphene quantum dots (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -GQD high entropy oxide composites increased the capacity by 498F / g, and N-doped graphene quantum dots (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 The capacity of the HS-GQD high-entropy oxide composite increased by 420.6 F / g.
[0126] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 The cyclic voltammetry curves of the BHS-GQD electrode at different scan rates are shown in Figure 2. Fig.13As shown, the results show that the redox peak pair indicates that Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQDs have pseudocapacitive characteristics, which mainly come from the redox reaction of metal ions in high-entropy oxides.
[0127] Example 6: Preparation of supercapacitor
[0128] Take the (Nb prepared in Example 5 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD electrode sheet, prepare super supercapacitor, the steps are as follows:
[0129] Two pieces (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD electrode sheets are used as the two electrodes of supercapacitors, PVA / Li 2 SO 4 The gel was used as the electrolyte to assemble into a symmetrical solid-state supercapacitor.
[0130] PVA / Li 2 SO 4 Preparation of gel electrolyte: 2.0 g polyvinyl alcohol (PVA) and 10 mL 2 mol / L Li 2 SO 4 The solution was poured into 20 mL of ultrapure water and stirred on a heating mantle at 75 °C until the solution became clear and transparent. After cooling to room temperature, PVA / Li 2 SO 4 gel.
[0131] (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2 O 4 -BHS-GQD / / (Nb 0.32 V 0.17 Mo 0.17 W 0.17 Co 0.17 ) 2O 4 -The energy density of BHS-GQD supercapacitors at different power densities is as follows Fig.14 As shown in the figure, at a power density of 900 W / kg, its energy can be as high as 153 Wh / kg, which is significantly higher than the energy density of aqueous supercapacitors based on current high-entropy oxide materials (Facile synthesis of high-entropy(Co0.2Cr0.2Fe0.2Mn0.2Ni0.2)3O4 nanopowders and their electrochemicalproperties as supercapacitor electrode;doi.org / 10.1016 / j.est.2023.109182) (at a power density of 746 W / kg, the energy density reaches 24 Wh / kg).
[0132] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a high entropy oxide composite, characterized in that: The method comprises: (1) mixing a cobalt ion salt, a tungsten ion salt, a vanadium ion salt, a niobium ion salt and a molybdenum ion salt in a molar ratio of 0.15-0.2:0.15-0.2:0.15-0.2:0.31-0.34:0.15-0.2, dissolving the mixture in a graphene quantum dot solution, and stirring the mixture to obtain a mixed solution; (2) using cotton to absorb the mixed solution and drying to obtain cotton adsorbed with metal ions and graphene quantum dots; wherein the mass ratio of metal salt, graphene quantum dots and cotton is 0.8-1.2:0.6-1.2:0.9-1.3; (3) Cotton adsorbed with metal ions and graphene quantum dots is annealed to prepare high entropy oxide.
2. The method according to claim 1, characterized in that The preparation method of graphene quantum dots comprises: One or more of citric acid, serine, histidine and boric acid are dissolved in water and heated for reaction to obtain; Optionally, citric acid is dissolved in water, and the ratio of citric acid to water is 18-19.5 g: 45-60 mL; Optionally, citric acid, serine and histidine are dissolved in water, and the dosage ratio of citric acid, serine, histidine and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 45-60 mL; Optionally, citric acid, serine, histidine and boric acid are dissolved in water, and the dosage ratio of citric acid, serine, histidine, boric acid and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 0.8-1.5 g: 45-60 mL; Optionally, the heating reaction is carried out at 170-200° C. for 2-4 hours.
3. The method according to claim 1, characterized in that The cobalt ion salt includes one or more of cobalt chloride, cobalt nitrate, and cobalt sulfate; The tungsten ion salt includes one or more of tungsten hexachloride, sodium metatungstate, and sodium tungstate dihydrate; The vanadium ion salt includes one or more of vanadium chloride, ammonium metavanadate, and sodium vanadate hydrate; The niobium ion salt includes one or more of niobium chloride, niobium oxalate, and ammonium niobate oxalate hydrate; The molybdenum ion salt includes one or more of sodium molybdate, molybdenum pentachloride, and ammonium molybdate.
4. The method according to claim 1, characterized in that Annealing is carried out at 800-900°C for 2-5 hours.
5. A high entropy oxide prepared by the method according to any one of claims 1 to 4.
6. Use of the method according to any one of claims 1 to 4 or the high entropy oxide according to claim 5 in the preparation of electronic components.
7. The use according to claim 6, characterized in that: The electronic components include batteries and capacitors.
8. A supercapacitor, characterized in that: The method for preparing the supercapacitor comprises: The high entropy oxide, carbon black and polyvinylidene fluoride described in claim 5 are dispersed in n-methyl-2-pyrrolidone to obtain an electrode slurry; the electrode slurry is coated on the surface of a titanium sheet to obtain an electrode sheet; two electrode sheets are used as electrodes and PVA / Li2SO4 gel is used as an electrolyte to form a symmetrical solid-state supercapacitor; Optionally, the mass ratio of high entropy oxide, carbon black and polyvinylidene fluoride is 70-90:5-15:5-15; Optionally, the mass density of the electrode slurry on the surface of the electrode sheet is 1.5 to 2.5 mg / cm.
9. A method for improving the performance of a supercapacitor, characterized in that: Preparation of supercapacitors using high entropy oxides; The preparation method of the high entropy oxide comprises: (1) mixing a cobalt ion salt, a tungsten ion salt, a vanadium ion salt, a niobium ion salt and a molybdenum ion salt in a molar ratio of 0.15-0.2:0.15-0.2:0.15-0.2:0.31-0.34:0.15-0.2, dissolving the mixture in a graphene quantum dot solution, and stirring the mixture to obtain a mixed solution; (2) using cotton to absorb the mixed solution and drying to obtain cotton adsorbed with metal ions and graphene quantum dots; wherein the mass ratio of metal salt, graphene quantum dots and cotton is 0.8-1.2:0.6-1.2:0.9-1.3; (3) Cotton adsorbed with metal ions and graphene quantum dots is annealed to prepare high entropy oxide.
10. The method according to claim 9, characterized in that The preparation method of graphene quantum dots comprises: Dissolving any one or more of citric acid, serine, histidine and boric acid in water and heating for reaction to obtain; Optionally, citric acid is dissolved in water, and the ratio of citric acid to water is 18-19.5 g: 45-60 mL; Optionally, citric acid, serine and histidine are dissolved in water, and the ratio of citric acid, serine, histidine and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 45-60 mL; Optionally, citric acid, serine, histidine and boric acid are dissolved in water, and the dosage ratio of citric acid, serine, histidine, boric acid and water is 18-19.5 g: 1.8-2.4 g: 15-16 g: 0.8-1.5 g: 45-60 mL; Optionally, the heating reaction is carried out at 170-200° C. for 2-4 hours.
Citation Information
Patent Citations
Method of graphene quantum dot reinforced metal oxide supercapacitor electrode material
CN110335765A
High entropically stabilized metal oxides@reduced graphene oxide (HEO@rgo) nanocomposite and method for synthesis thereof
IN202341054382A
Electrode material for supercapacitor utilizing cobalt oxide-nanocarbon composite consolidated active-conducting materials structured core-shell quantum dots type and fabrication process thereof
KR1020170092403A
High entropy composite oxide, manufacturing method thereof, and anode materials comprising the same
US20220135426A1